Variants of genes implicated in type 1 interferon pathway and B-cell activation modulate the EULAR response to rituximab at 24 weeks in rheumatoid arthritis. Issue 2 (28th September 2017) - Juge, Pierre-Antoine; Gazal, Steven; Constantin, Arnaud; Mariette, Xavier; Combe, Bernard; Tebib, Jacques; Dougados, Maxime; Sibilia, Jean; Le Loet, Xavier; Dieudé, Philippe
Abstract : Background: The type 1 interferon (IFN) pathway has been identified to potentially affect the response to rituximab (RTX) for rheumatoid arthritis (RA), which suggests the contribution of type 1 IFN pathway genes such as IFN regulatory factor 5 and 7 ( IRF5 and IRF7 ), tyrosine kinase 2 ( TYK2 ), signal transducer and activator of transcription 4 ( STAT4 ) and osteopontin ( SPP1 ). Our objective was to study functional variants of these IFN pathway genes as predictors of the European League Against Rheumatism (EULAR) response to RTX for RA at week 24 (W24). Methods: Logistic regression analysis with a stepwise multivariate model adjusted for sex, age and DAS28-CRP (Disease Activity Score in 28 joints with C reactive protein) in 115 patients from the SMART randomised studywas used to analyse the association between the candidate variants and W24 EULAR response. Because the variant TNFSF13B rs9514828 was previously found associated with RTX response in the same population, it was included in the analysis. Results: The combination of IRF5 rs2004640, SPP1 rs9138 and TNFSF13B rs9514828 was strongly associated with good/moderate EULAR response to RTX at W24: p=9.34×10 −6, OR 11.37 (95% CI 4.03 to 35.28), positive predictive value 91% and negative predictive value 54%. Conclusion: Our results support the contribution of the IRF5, SPP1 and TNFSF13B genotypic combination in the response to RTX for RA at W24.